OPTIMASI RUTE SALES COVERAGE MENGGUNAKAN ALGORITMA CHEAPEST INSERTION HEURISTIC DAN LAYANAN GOOGLE MAPS API - Erwin Yulianto; Awan Setiawan (INTERNAL (Information System Journal), 2018)
Traveling Salesman Problem (TSP) is one of the distribution issues which is long discussed in the optimization review, where the review problem is how a salesman visits the entire travel route within the coverage area and returns to the starting point of departure with the rule that no destination should be visited more than once. PT. Panjunan is a company engaged in the products distribution of various principles. Currently the managing process of customer location data at the company is still not maximal due to the absence of calculations in every daily visit routes so it impact on the effectiveness of time. In addition, the absence of visualization of real customer data on the field leads to the error distribution and marketing of goods which is uneven, not on target and impact on the decline in sales value. One of the techniques used to accelerate the search solutions of TSP problems is to use an insertion algorithm, or also called the Cheapest Insertion Heuristic (CIH) algorithm. The discussion of this research is to study and apply CIH algorithm in determining the optimization of daily sales traffic route with the aim of this research is to make daily trip route optimization program by applying Cheapest Insertion Heuristics algorithm and provide real customer data visualization on original map in the field as analysis material for operational team and management by utilizing Google Maps API service. System development method used in this research using waterfall model with implementation tools is laravel framework and mySQL as DBMS.